Partnership Communication Plan to Support the Implementation of Holistic-Integrative Early Childhood Education (PAUD HI). - Dhian Gowinda Luh Safitri (SEA-CECCEP, 2021)
The government has issued a policy requiring that Early Childhood Education Institutions must be conducted in a holistic-integrative manner to improve the quality of Early Childhood Education, provide a comprehensive, quality service, and involve all related education stakeholders.  As a matter of fact, that the partnership between school, family, and community could enhance student's learning, accommodate the diverse needs of the student and bring an inclusive culture in education, it's essential for the teacher to develop communication partnership plan. This study was conducted in a systematic review with a qualitative approach. The communication values that can be implemented to develop an effective partnership are include understanding and respecting, openness, mutual trust, and commitment. The possible obstacles to implement this communication partnership plan components include a judgmental attitude when working with family and community, school as a hostile environment, the assumption that family and community are less able in the educational process, and lack of teacher partnership training.